Macrophage-Derived Exosomal Mir-155 Regulating Cardiomyocyte Pyroptosis and Hypertrophy in Uremic Cardiomyopathy - Wang, Bin; Wang, Ze-Mu; Ji, Jia-Ling; Gan, Weihua; Zhang, Aiqing; Shi, Hao-Jie; Wang, Hao; Lv, Linli; Li, Zuolin; Tang, Taotao; Du, Jie; Wang, Xiaonan H.; et al. (JACC. Basic to translational science, 2020)
[Display omitted] •miR-155 was synthesized and loaded into exosomes in increased infiltration of macrophages in a uremic heart.•The released exosomal fusion with the plasma membrane leads to the release of miR-155 into the cytosol and translational repression of forkhead transcription factors of the O class in cardiomyocytes.•Macrophage-derived miR-155–containing exosomes promoted cardiomyocyte pyroptosis and uremic cardiomyopathy changes (cardiac hypertrophy and fibrosis) by directly targeting FoxO3a in uremic mice. Inhibiting secretion from macrophage-derived miR-155–containing exosomes represents a novel therapeutic strategy for the management of uremic cardiomyopathy. miR-155 was synthesized and loaded into exosomes in increased infiltration of macrophages in a uremic heart. The released exosomal fusion with the plasma membrane leads to the release of miR-155 into the cytosol and translational repression of forkhead transcription factors of the O class (FoxO3a) in cardiomyocytes. Finally, macrophage-derived miR-155–containing exosomes promoted cardiomyocyte pyroptosis and uremic cardiomyopathy changes (cardiac hypertrophy and fibrosis) by directly targeting FoxO3a in uremic mice.